2022
DOI: 10.3389/fpubh.2022.838733
|View full text |Cite
|
Sign up to set email alerts
|

Can Basic Medical Insurance Reduce Elderly Family Income Inequality in China?

Abstract: Basic medical insurance is the critical medical security system to realize common prosperity in China. This study explores the impact of basic medical insurance on elderly family income inequality in China using the China Family Panel Studies (CFPS) data in 2018. Our finding shows that basic medical insurance is significantly negatively correlated with elderly family income inequality, indicating basic medical insurance has a positive impact on narrowing the elderly family income inequality. The heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Expenditure is significantly and negatively correlated with health, as the more items and amounts a household spends, the less it must spend on savings and investments, the less it is able to invest in health and fight disease, and the more it is vulnerable to health risks ( 42 ). In addition, medical insurance is significantly and positively correlated with health, and medical insurance has the function of defusing and hedging health risk ( 43 ). Building structure is positively correlated with health, firstly because a safer housing structure indicates a higher level of household income and the ability to cope with disease crises ( 44 ), and secondly because households with a safe housing structure can withstand the risks to human health caused by climatic disasters and environmental degradation ( 45 ).…”
Section: Empirical Analysis and Discussionmentioning
confidence: 99%
“…Expenditure is significantly and negatively correlated with health, as the more items and amounts a household spends, the less it must spend on savings and investments, the less it is able to invest in health and fight disease, and the more it is vulnerable to health risks ( 42 ). In addition, medical insurance is significantly and positively correlated with health, and medical insurance has the function of defusing and hedging health risk ( 43 ). Building structure is positively correlated with health, firstly because a safer housing structure indicates a higher level of household income and the ability to cope with disease crises ( 44 ), and secondly because households with a safe housing structure can withstand the risks to human health caused by climatic disasters and environmental degradation ( 45 ).…”
Section: Empirical Analysis and Discussionmentioning
confidence: 99%
“…The average life expectancy is a key indicator to measure the health level of the residents of a region, a country, or a nation. It can clearly reflect the quality of life of a society and is also an important embodiment of common prosperity (Pu et al, 2022 ).…”
Section: Comprehensive Evaluation Index System For Cplmentioning
confidence: 99%
“…Health shock is widely defined as sudden health deterioration caused by diseases or accidents (11,36). Some previous studies used self-reported health (37), sickness in the past 4 weeks (37) and hospitalization in the past year (38), the proportion of medical expenditures (39) and other indicators as standards. However, the measurement of these indicators did not subdivide the types of health shocks.…”
Section: Independent Variablementioning
confidence: 99%
“…Control variables were mainly selected from personal and family characteristics according to previous literature (36,37,39). The level of personal characteristics included: (1) The age of the respondents (age) was a continuous variable; (2) Marital status (marry) was a binary variable.…”
Section: Control Variablesmentioning
confidence: 99%